2008
DOI: 10.1523/jneurosci.4738-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Homer3 by Calcium/Calmodulin-Dependent Kinase II Regulates a Coupling State of Its Target Molecules in Purkinje Cells

Abstract: Homer proteins are components of postsynaptic density (PSD) and play a crucial role in coupling diverse target molecules. However, the regulatory aspect of Homer-mediated coupling has been addressed only about a dominant-negative effect of Homer1a, which requires de novo gene expression. Here, we present evidence that Homer-mediated coupling is regulated by its phosphorylation state. We found that Homer3, the predominant isoform in Purkinje cells, is phosphorylated by calcium/calmodulin-dependent protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 56 publications
(68 reference statements)
3
61
0
Order By: Relevance
“…In addition, we confirmed the effect of IRBIT on CaMKIIα kinase activity using recombinant Homer 3 protein, which is a substrate for CaMKIIα (31). IRBIT significantly inhibited the phosphorylation of Homer 3 in a concentration-dependent manner ( Fig.…”
Section: +supporting
confidence: 71%
“…In addition, we confirmed the effect of IRBIT on CaMKIIα kinase activity using recombinant Homer 3 protein, which is a substrate for CaMKIIα (31). IRBIT significantly inhibited the phosphorylation of Homer 3 in a concentration-dependent manner ( Fig.…”
Section: +supporting
confidence: 71%
“…Recent studies have suggested that Homer 3 interacts with amyloid precursor protein (5961) and inhibits the production of Aβ (5961). In Purkinjee neurons, Homer 3 interacts with mGluR1alpha and this interaction is regulated by phosphorylation (62). Our findings (RNAseq, qPCR and Western) revealed that a specific member of the Homer family of proteins, Homer 3, is upregulated in the mPFC within the first hour following CFC training.…”
Section: Discussionmentioning
confidence: 99%
“…13-15 Multiple members of the TRPC subfamily of TRP channels have been shown to require the scaffolding protein Homer 1 for proper function 16,17 and several groups have shown that Homer scaffolds associate with Drebrin through an interaction mediated by two Homer-binding sites within the Drebrin C-terminal domain. 18-20 We made the unexpected observation that Drebrin is abundantly expressed in SMCs and is upregulated in response to arterial injury. Because neointimal hyperplasia, a process which involves both SMC migration and proliferation, may involve SMC TRP channels 15 and because TRPC channel function is regulated by the Drebrin-binding protein Homer, 16 we tested whether Drebrin affects SMC proliferation and migration through its interaction with Homer and/or F-actin.…”
Section: Introductionmentioning
confidence: 99%